A Study of Discrete Insurance Risk Model and its Ruin Probability - GOH, HUI QIN; Dr. Kavikumar Jacob (Enhanced Knowledge in Sciences and Technology, 2022)
This study reflects on the risk management perspective especially in terms of insurance risk models. From the scenery of the insurance company, the main idea of the risk model looks into how risks affect the probability of ruin. The probability of ruin is determined using different risk models such as Poisson and Binomial distributions. Therefore the main objectives of this study are to study the discrete-time risk model and to minimize the probability of ruin which the main scope being the probability of ruin being calculated using the discrete-time model. From the study, we found that there are several different ways to reduce the probability of ruin such as reinsurance and reinvestment. There are many different types of research out there that apprehend the findings. There could be future work to focus on especially towards the future of reinvestment as a great way to reduce the probability of ruin.